Oil Products and the Volatility Index: Bivariate Volatility Relationships Within a T-GARCH Model - Ben Sita, Bernard (2017)
I provide, in this paper, evidence on the contribution of crude oil excess volatility to the volatility index. Crude oil leads the volatility index by 16 basis points (BP) 6 months ahead of time. This leadership is reversal and covers the period from January 21, 2000 to the end of 2011. The lagged and the contemporaneous effects amount to 35BP and 21BP, respectively. Moreover, I provide volatility quantities that would spill over from crude oil to refined oil products, and from crude oil to the volatility index. Based on a T-GARCH model augmented with correlation-weighted volatility ratios, I document quantities that can be useful in program trading.